2017
DOI: 10.1016/j.antiviral.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

T-cell immunity of SARS-CoV: Implications for vaccine development against MERS-CoV

Abstract: Over 12 years have elapsed since severe acute respiratory syndrome (SARS) triggered the first global alert for coronavirus infections. Virus transmission in humans was quickly halted by public health measures and human infections of SARS coronavirus (SARS-CoV) have not been observed since. However, other coronaviruses still pose a continuous threat to human health, as exemplified by the recent emergence of Middle East respiratory syndrome (MERS) in humans. The work on SARS-CoV widens our knowledge on the epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
394
2
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(435 citation statements)
references
References 126 publications
25
394
2
14
Order By: Relevance
“…21 Additionally, lymphocytopenia is also common in the critically ill patients with MERS infection, which is the result of apoptosis of lymphocytes. 22,23 Therefore, we postulate that necrosis or apoptosis of lymphocytes also induces lymphocytopenia in critically ill patients with SARS-CoV-2 infection. In a previous study, mainly in non-critical patients infected with SARS-CoV-2, 35% of patients had only mild lymphocytopenia, 2 suggesting that the severity of lymphocytopenia reflects the severity of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…21 Additionally, lymphocytopenia is also common in the critically ill patients with MERS infection, which is the result of apoptosis of lymphocytes. 22,23 Therefore, we postulate that necrosis or apoptosis of lymphocytes also induces lymphocytopenia in critically ill patients with SARS-CoV-2 infection. In a previous study, mainly in non-critical patients infected with SARS-CoV-2, 35% of patients had only mild lymphocytopenia, 2 suggesting that the severity of lymphocytopenia reflects the severity of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to T lymphocytes might be an important factor leading to exacerbations of patients. 25 The low absolute value of lymphocytes could be used as a reference index in the diagnosis of new coronavirus infections in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The first SARS-CoV DNA vaccine was tested in humans only 19 months after the virus sequence was published [38], while the DNA vaccine GLS-5300, the first MERS-CoV vaccine, went to clinical trials in 2016 [39]. In addition to these conventional vaccines, Liu et al analyzed the T cell epitopes of SARS-CoV and MERS-CoV, revealed the potential cross-reactivity of the coronaviruses, and assessed the possibility of developing universal vaccines against coronavirus infections [40].…”
Section: Research and Development Of Vaccinesmentioning
confidence: 99%